IDENTIFIKASI KARAKTERISTIK ORGANISASI YANG DOMINAN DALAM MANAJEMEN RUMAH SAKIT TNI-AU TINGKAT-II : STUDI KASUS RS Dr. M. SALAMUN BANDUNG - Hariandja, Evo S. (Industrial and Systems Engineering Assessment Journal (INASEA), 2005)
Indonesian Air Force Hospital Level II Dr. M. Salamun, Bandung as medical services also serve the members and families of Indonesia Forces and community. This research aims to identify the dominant characteristics of organization through perception survey to personnel of that hospital by using the rules in that hospital. Data process using factor analysis that describe dominant characteristics that have unit of data observation, analyze some manifest variables, and combine into few latent variables but have significant information that needed.